‘Kitchen and cooking,’ a serious game for mild cognitive impairment and Alzheimer’s disease: a pilot study - Manera, Valeria; Petit, Pierre-David; Derreumaux, Alexandre; Orvieto, Ivan; Romagnoli, Matteo; Lyttle, Graham; David, Renaud; Robert, Philippe H. (Frontiers in Aging Neuroscience, 2015)
Recently there has been a growing interest in employing serious games for the assessment and rehabilitation of elderly people with Mild Cognitive Impairment (MCI), Alzheimer’s disease (AD) and related disorders. In the present study we examined the acceptability of ‘Kitchen and cooking’ - a serious game developed in the context of the EU project VERVE (http://www.verveconsortium.eu/) - in these populations. In this game a cooking plot is employed to assess and stimulate executive functions (such as planning abilities) and praxis. The game is installed on a tablet, to be flexibly employed at home and in nursing homes. 21 elderly participants (9 MCI and 12 AD, including 14 outpatients and 7 patients living in nursing homes, as well as 11 apathetic and 10 non-apathetic) took part in a 1-month trail, including a clinical and neuropsychological assessment, and 4-week training where the participants were free to play as long as they wanted on a personal tablet. During the training, participants met once a week with a clinician in order to fill in self-report questionnaires assessing their overall game experience (including acceptability, motivation, and perceived emotions). The results of the self reports and of the data concerning game performance (e.g. time spent playing, number of errors, etc) confirm the overall acceptability of Kitchen and cooking for both patients with MCI and patients with AD and related disorders, and the utility to employ it for training purposes. Interestingly, the results confirm that the game is adapted also to apathetic patients.